Searching for the Cinaedus in Ancient Rome - Gazzarri, Tommaso; Weiner, Jesse (Mnemosyne, Supplements, 2023)
The cryptic figure of the cinaedus recurs in both the literature and daily life of the Roman world. His afterlife - the equally cryptic catamite - appears to be well and alive as late as Victorian England. But who was the cinaedus ? Should we think of a real group of individuals, or is the term but a scare name to keep at bay any form of threating otherness? This book, the first coherent collection of essays on the topic, addresses the matter and fleshes out the complexity of a debate that concerns not only Roman cinaedi but the foundations of our theoretical approach to the study of ancient sexuality.